2019
DOI: 10.1371/journal.pone.0221597
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio predicts early worsening in stroke due to large vessel disease

Abstract: Background Inflammation plays an important role in atherosclerosis and its complications. Since a dysregulated inflammatory response is associated with early neurological deterioration (END), serum neutrophil-to-lymphocyte ratio (NLR) could be a marker of END as well. Aim In this study, we evaluated the relationship between the serum NLR and END in patients with ischemic stroke due to large-artery atherosclerosis (LAA). Methods We evaluated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In the subgroup analysis according to the type of stroke, there were three studies on hemorrhagic stroke [ 19 , 20 , 22 ], including 830 patients, of whom 237 developed END, and six studies on ischemic stroke [ 15 18 , 21 , 23 ], including 1894 patients, of whom 505 developed END. The NLR levels in patients with hemorrhagic stroke who developed END were similar to those without END (SMD = 0.84, CI 95% = −0.10-1.77, P value = 0.07).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subgroup analysis according to the type of stroke, there were three studies on hemorrhagic stroke [ 19 , 20 , 22 ], including 830 patients, of whom 237 developed END, and six studies on ischemic stroke [ 15 18 , 21 , 23 ], including 1894 patients, of whom 505 developed END. The NLR levels in patients with hemorrhagic stroke who developed END were similar to those without END (SMD = 0.84, CI 95% = −0.10-1.77, P value = 0.07).…”
Section: Resultsmentioning
confidence: 99%
“…After screening of the remaining 17 studies in full text, three studies without any data on NLR and END, two studies with missing SD data, one study including stroke patients suffering from cancer, one study without a control group, and one review article were excluded. Finally, nine articles were included in our study [15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical data collection included prior medical history (hypertension, diabetes mellitus, and atrial fibrillation), result of routine blood test, partial blood biochemical examination (levels of glucose, lipids, albumin, homocysteine, C-reactive protein, serum amyloid A), head MRI, chest X-ray photographs or pulmonary CT, and NIHSS at admission. The neutrophil-to-lymphocyte ratio (NLR), known as a systemic inflammation and infection mark, has shown an excellent power for predicting pneumonia ( Curbelo et al, 2017 ; Lee et al, 2016 ; Nam et al, 2019 ). Thus, we also evaluated the impact of NLR, as well as neutrophil-to-monocyte ratio (NMR), on patients with SAP.…”
Section: Methodsmentioning
confidence: 99%
“…Nam et al reported that NLR level was independently associated with END events in patients with LAAS. The mechanism might be involved in the degree of large artery stenosis, the number of stenotic lesions, and the stability of atherosclerotic plaque ( Nam et al, 2019 ). The NLR level was also related to END in patients with single subcortical infarctions which were defined as an infarct in the area of penetrating arteries and its prognosis is relatively favorable ( Nam et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%